CHARGE Syndrome from Pediatric Endocrinologist Perspective: Clinical Case - Kristina D. Kokoreva; Natalia N. Volevodz (Вопросы современной педиатрии, 2024)
Background. CHARGE syndrome is an autosomal dominant disease with population frequency of 1 case per 8500–15,000 newborns. The cause of this disease is nucleotide changes in the CHD7 gene. The “major” criteria for the syndrome are eye coloboma, choanal atresia or stenosis, midline defects (cleft lip and/or palate), and congenital malformations of outer, middle, and inner ear. CHARGE syndrome is characterized by significant clinical polymorphism complicating its diagnosis. Clinical case description. The boy, 5 years old, has been referred to endocrinologist due to unilateral cryptorchidism since birth. We have revealed face asymmetry, auricles abnormalities, hypoplastic scrotum and absence of one testicle in the scrotum during examination. Retinal coloboma, bilateral hearing loss, operated cleft lip and palate, difficulties with feeding, chewing, and swallowing, mental retardation and facial paralysis were also noted. CHARGE syndrome was clinically diagnosed, and later it was confirmed by molecular genetic testing: previously described pathogenic heterozygous nucleotide variant chr8:60838202C>T (HG38) in exon 19 of the CHD7 gene was revealed. Conclusion.  Manifestations of CHARGE syndrome vary from patient to patient, thus, molecular genetic confirmation of the diagnosis is crucial. Patients with CHARGE syndrome require follow-up by multi-disciplinary team, and the endocrinologist is usually admitted with complaints on growth retardation, delayed puberty, cryptorchidism and hypoplastic external genitalia. It is possible to suspect hypogonadotropic hypogonadism in a boy with CHARGE syndrome at pre-pubertal age in case of its combination with one- or bilateral cryptorchidism, hypoplastic external genitalia and low inhibin B level.